2007
DOI: 10.1105/tpc.107.052738
|View full text |Cite
|
Sign up to set email alerts
|

Polar Growth in the Infectious Hyphae of the PhytopathogenUstilago maydisDepends on a Virulence-Specific Cyclin

Abstract: The maize smut fungus Ustilago maydis switches from yeast to hyphal growth to infect maize (Zea mays) plants. This switching is promoted by mating of compatible cells and seems to be required for plant penetration. Although many genes distinctively expressed during this dimorphic switch have been identified and shown to be essential for the infection process, none seems to be explicitly required for polar growth control. Here, we report the characterization of pcl12, encoding a cyclin that interacts specifical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 58 publications
1
31
1
Order By: Relevance
“…In A. nidulans, the orthologues of ScPho85, An-PhoA and An-PhoB, are essential and play a role in development but not in phosphate acquisition (Bussink and Osmani, 1998;Dou et al, 2003). In Ustilago maydis, UmPHO85 (UnCDK5) is also essential and is shown to function in polarity maintenance and virulence but not in phosphate acquisition (Castillo-Lluva et al, 2007;Flor-Parra et al, 2007). Although we showed that CnPho85 (and CnPho80) is involved in the regulation of the CnPHO system (Figs.…”
Section: The Cnpho System and The Pathogenicity Of C Neoformansmentioning
confidence: 78%
“…In A. nidulans, the orthologues of ScPho85, An-PhoA and An-PhoB, are essential and play a role in development but not in phosphate acquisition (Bussink and Osmani, 1998;Dou et al, 2003). In Ustilago maydis, UmPHO85 (UnCDK5) is also essential and is shown to function in polarity maintenance and virulence but not in phosphate acquisition (Castillo-Lluva et al, 2007;Flor-Parra et al, 2007). Although we showed that CnPho85 (and CnPho80) is involved in the regulation of the CnPHO system (Figs.…”
Section: The Cnpho System and The Pathogenicity Of C Neoformansmentioning
confidence: 78%
“…maydis strains are listed in Table 1. Manipulations with U. maydis, culture methods, gene disruption and gene transfer procedures, survival after DNA damage, and plant infections have been described previously (Castillo-Lluva and Pé rez-Martín, 2005;Flor-Parra et al, 2007;Mielnichuk and Pé rez-Martín, 2008;Mielnichuk et al, 2009). Protein extracts, immunoprecipitations, and immunoblot analysis were performed as described previously (García-Muse et al, 2004;Sgarlata and Pé rez-Martín, 2005).…”
Section: Ustilago Maydis Genetic Methodsmentioning
confidence: 99%
“…Plant infection and charcoal assays were described previously (Flor-Parra et al, 2007). Staining of infected plant samples with Chlorazole Black E was done as described previously (Brachmann et al, 2003).…”
Section: Infection Assaysmentioning
confidence: 99%
“…Which mechanisms are used by the bW-bE heterodimer to induce the hyperpolarized growth and to arrest the cell cycle in the infectious hypha and at which stage this occurs are unknown, but these issues are currently being studied. For example, recent results from our laboratory indicated that the activation of hyperpolarized growth after bW-bE heterodimer formation is dependent on the U. maydis ortholog of the cyclin-dependent kinase Cdk5, a well-known regulator of neuron development in mammals (Alvarez-Tabares and Perez-Martin, 2008;Castillo-Lluva et al, 2007;Flor-Parra et al, 2007).…”
Section: Introductionmentioning
confidence: 99%